Revisiting high harmonic generation in nonlinear epsilon-near-zero metamaterials - Barbet, Geoffrey Pascal (Nanyang Technological University, 2024)
Efficient nonlinear processes are required in many applications in photonics and so have been a field of interest for a few decades now. Different approaches have been followed, the first one being the investigation of natural nonlinear material. However, their inherently weak nonlinear responses have led to bulky systems and complex setups with large size samples and phase matching optical techniques to get sufficient efficiency, hence the need to develop new devices with lower power consumption and smaller footprints. Recent work has shown the development of a new kind of nanostructured media, called metamaterials, with unprecedented effective linear and nonlinear properties and flexibility. One of many ways to enhance light-matter interactions is to bring the permittivity of a media to zero. This so-called Epsilon-Near-Zero (ENZ) material supports exceptional features such as the decoupling of spatial and temporal field variations, light squeezing, enhanced harmonic generation, phase mismatch–free nonlinear propagation, photonic doping, etc. But despite the progress in this field, some limitations remain. Indeed, ENZ properties only rise at oblique incidence and are currently limited to certain domains of frequencies. The work presented in this thesis has been to overcome those limitations while utilizing the unusual nonlinear ENZ features at their maximum potential, while keeping in mind two requirements: high efficiency and ease of fabrication. Following that logic, the first study has been to design a microwave multilayer structure that produces high second harmonic generation for all angle of incidence. We have then extended the study to the mid-infrared frequencies where we utilized the huge nonlinear parameters of multiple quantum wells (MQW) to enhance the second harmonic response of intersubband transitions. The MQWs have also been coupled to nanoresonators so the device can perform at normal incidence. Finally, the third project focused on the design of a phase mismatch-free media at microwave frequency. Counterpropagating waves and ENZ frequency set to the second harmonic frequency produce a fully matched medium where the nonlinear process can build up constructively over a large distance.